The effect of coil type and limb dominance in the assessment of lower-limb motor cortex excitability using TMS. (23rd April 2019) - Dharmadasa, Thanuja; Matamala, José M.; Howells, James; Simon, Neil G.; Vucic, Steve; Kiernan, Matthew C.
Highlights: Optimal coil type to assess lower-limb cortical function was determined with TT-TMS. Key differences were found in generated cortical parameters between the coil types. The double cone coil showed greatest efficacy, generating lowest motor thresholds. Intracortical facilitation was comparatively greater using the double cone coil. There was no cortical asymmetry between dominant and non-dominant hemispheres. Abstract: Purpose: Clinical application of transcranial magnetic stimulation (TMS) has rapidly increased but the majority of studies have targeted upper limb muscles, with few exploring the lower-limb. Differences of coil choice have added to methodological difficulties of lower-limb studies and have challenged consistent interpretation of these parameters. The aims of this study were to determine the optimal coil choice for assessing lower-limb cortical excitability and assess laterality of normal cortical function. Methods: 69 recordings were undertaken from the tibialis anterior muscle from 48 healthy participants. Three coil types currently used in lower-limb studies (90 mm circular; 70 mm figure-of-8; and 110 mm double cone) were explored using single pulse TMS and paired-pulse threshold tracking TMS (TT-TMS) paradigms, with peripheral function also assessed. Cortical symmetry was ascertained with bilateral recordings (dominant versus non-dominant muscles). Results: The double-cone coil showed greatest efficacy, with significantly lower resting motor thresholds (49.0 ± 2.3%, p< 0.0005) and greater intracortical facilitation compared to the alternate coil choices. Using the double-cone coil, paired-pulse TT-TMS generated an averaged short interval intracortical inhibition of 11.3 ± 1.2%, with an averaged intracortical facilitation of -6.1 ± 1.9%. There were no differences between dominant and non-dominant hemispheres. Conclusions: The present study identified key differences in cortical parameters between the currently utilised coils for lower-limb TMS. Specifically, this indicates the importance of standardizing the lower-limb TMS protocol, particularly for accurate interpretation in disease pathology.